Determinants for Adopting ICTs by Livestock Farmers in Barnala District, Punjab - Singh, Suryendra; Tanwar, Prahlad Singh; Sharma, Anjuly (Indian Journal of Extension Education, 2023)
A study was conducted to determine the propensity of livestock farmers to adopt ICTs in the Barnala district of Punjab, India. The convenience sampling technique was used to select 60 livestock farmers from all three blocks of the Barnala district and the data was collected from respondent livestock farmers via direct interview using a pre-formulated schedule. Livestock farmers were using ICT (GADVASU apps) to enhance their farm income. The commonly used ICT tools were mobile phones, Internet browsing, newspapers, and television. The use of ICT (GADVASU apps) by livestock farmers was effective as it contributed to enhancing livestock productivity. Socio-economic and institutional factors significantly influenced the use and adoption of ICTs by livestock farmers. Tobit analysis results indicated that age, education level, herd size, and participation in extension activities were significant (p
Keywords: Socio-economic and institutional factors; Propensity to adopt ICTs; Tobit analysis